Effects of cis-regulatory variation differ across regions of the adult human brain - Buonocore, Federica; Hill, Matthew J.; Campbell, Colin D.; Oladimeji, Paul B.; Jeffries, Aaron R.; Troakes, Claire; Hortobagyi, Tibor; Williams, Brenda P.; Cooper, Jonathan D.; Bray, Nicholas J. (Human molecular genetics, 2010)
Cis-regulatory variation is considered to be an important determinant of human phenotypic variability, including susceptibility to complex disease. Recent studies have shown that the effects of cis-regulatory polymorphism on gene expression can differ widely between tissues. In the present study, we tested whether the effects of cis-regulatory variation can also differ between regions of the adult human brain. We used relative allelic expression to measure cis-effects on the RNA expression of five candidate genes for neuropsychiatric illness (ZNF804A, NOS1, RGS4, AKT1 and TCF4) across multiple discrete brain regions within individual subjects. For all five genes, we observed significant differences in allelic expression between brain regions in several individual subjects, suggesting regional differences in the effects of cis-regulatory polymorphism to be a common phenomenon. As well as highlighting an important caveat for studies of regulatory polymorphism in the brain, our findings indicate that it is possible to delineate brain areas in which cis-regulatory variants are active. This may provide important insights into the fundamental biology of neuropsychiatric phenotypes with which such variants are associated.